Numerical Study on the Transport and Settlement of Larval Hippocampus trimaculatus in the Northern South China Sea - Chi Zhang; Zengan Deng (Journal of Marine Science and Engineering)
The three-spot seahorse (Hippocampus trimaculatus) is an economically important marine species in the northern South China Sea (NSCS). However, due to overfishing and marine environmental changes, its wild populations have been gradually depleted. To investigate the transport and settlement mechanisms of H. trimaculatus larvae in the NSCS, a physical–biological coupled model was developed based on the ocean model CROCO and the biological model Ichthyop for the period 2016–2018. The results indicate that the transport and settlement processes of larvae are primarily regulated by the combined influence of the South China Sea Warm Current, coastal upwelling, and Kuroshio intrusion. The larvae predominantly undergo short distance (0–300 km) and mid-short distance (300–600 km) transport, exhibiting significant spatial aggregation along coastal waters, particularly in the Gulf of Tonkin, the Pearl River Estuary, Shantou, Xiamen, and the western coast of Taiwan. Furthermore, extreme weather events, such as typhoons, significantly enhance larval settlement success rates. Notably, Typhoon Hato in August 2017 increased settlement success by 12.2%. This study elucidates the transport and settlement mechanisms of H. trimaculatus larvae, providing a scientific foundation for the conservation and management of its populations in the NSCS.